Kematangan Emosi, Efikasi Diri dan Perilaku Merokok Remaja Laki-Laki Usia 12-15 Tahun - ., Supeno; ., Suroso (Persona:Jurnal Psikologi Indonesia, 2015)
Emotional maturity, self-efficacy, and Smoking Behavior examined in acorrelational quantitative research. Subjects were 131 Adolescence on 12 – 15 Yearof Ages. Researcher developed two research instrument of measurement, namely thescale of smoking behavior and the scale of emotional maturity. Data of studyvariables were analyzed with the multiple regression analysis. The results of theanalysis are: 1) R = 0,181, F = 2,179, p = 0,177 (p > 0,05) showed no correlationof emotional maturity and self-efficacy with smoking behavior on 12 – 15 Year ofAges simultaneously, 2) r partial = - 0,173, p = 0,049 (p < 0,05) shows thecorrelation of emotional maturity with smoking behavior is a negative direction andlinear; 3) r partial = - 0,055, p = 0,534 (p > 0,05) shows no correlation self-efficacywith smoking behaviorKeywords : emotional maturity, self-efficacy, smoking behavior